Risk factors and timing of venous thromboembolism after radical cystectomy in routine clinical practice: a population‐based study. (7th March 2016) - Doiron, R. Christopher; Booth, Christopher M.; Wei, Xuejiao; Siemens, D. Robert
Abstract : Objective: To describe the risk factors and timing of perioperative venous thromboembolism (VTE) and its association with survival for patients undergoing radical cystectomy (RC) in routine clinical practice. Patients and Methods: The population‐based Ontario Cancer Registry was linked to electronic records of treatment to identify all patients who underwent RC between 1994 and 2008; VTE events were identified from hospital diagnostic codes. Multivariate logistic regression analysis was used to determine the factors associated with perioperative VTE. A Cox proportional hazards regression model explored the associations between VTE and survival. Results: Of the 3 879 patients included in the study, 3.6% (141 patients) were diagnosed with VTE at ≤1 month of their surgical admission date. This increased to 4.7% (181) at ≤2 months and 5.4% (211) at ≤3 months. In all, 55% of VTE events presented after hospital discharge. In multivariate analysis, factors associated with VTE included higher surgeon volume ( P = 0.004) and increased length of hospital stay (LOS; P < 0.001). Lymph node yield and adjuvant chemotherapy were not associated with VTE. VTE was associated with an inferior cancer‐specific survival [hazard ratio (HR) 1.35, 95% confidence interval (CI) 1.13–1.62] and overall survival (HR 1.27, 95% CI 1.08–1.49). Conclusions: Over half of VTE events in RC patients occur after hospital discharge, with a substantial incidence up to 3 months after surgery. Limited actionable risk factors for VTE were identified other than LOS. In this population‐based cohort, VTE was associated with inferior long‐term survival.